Psychometric properties of the Portuguese version of place attachment scale for youth in residential care - Magalhães, E. (2015)
Background: Although the significant scientific advances on place attachment literature, no instruments exist specifically developed or adapted to residential care. Method: 410 adolescents (11 - 18 years old) participated in this study. The place attachment scale evaluates five dimensions: Place identity, Place dependence, Institutional bonding, Caregivers bonding and Friend bonding. Data analysis included descriptive statistics, content validity, construct validity (Confirmatory Factor Analysis), concurrent validity with correlations with satisfaction with life and with institution, and reliability evidences. The relationship with individual characteristics and placement length was also verified. Results: Content validity analysis revealed that more than half of the panellists perceive all the items as relevant to assess the construct in residential care. The structure with five dimensions revealed good fit statistics and concurrent validity evidences were found, with significant correlations with satisfaction with life and with the institution. Acceptable values of internal consistence and specific gender differences were found. Conclusions: The preliminary psychometric properties of this scale suggest it potential to be used with youth in care.